2016
DOI: 10.1002/chem.201602130
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of U28 in the Aqueous Self‐Assembly of Uranyl Peroxide Nanocages

Abstract: For 11 years now, the structural diversity and aesthetic beauty of uranyl-peroxide capsules have fascinated researchers from the diverse fields of mineralogy, polyoxometalate chemistry, and nuclear fuel technologies. There is still much to be learned about the mechanisms of the self-assembly process, and the role of solution parameters including pH, alkali template, temperature, time, and others. Here we have exploited the high solubility of the UO2 (2+) /H2 O2 /LiOH aqueous system to address the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(117 citation statements)
references
References 59 publications
10
107
0
Order By: Relevance
“…Therefore, we suspect that there are encapsulated uranium ions. This has been observed in several single‐crystal structural studies , , …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, we suspect that there are encapsulated uranium ions. This has been observed in several single‐crystal structural studies , , …”
Section: Resultssupporting
confidence: 70%
“…It has also been shown that, under more acidic conditions, these capsules form with oxalate or pyrophosphate bridges . Mechanisms of cluster formation are not yet fully understood, but both “bottom‐up” cluster assembly (monomeric uranyl to cluster),, and top‐down assembly (studtite mineral to cluster) have been amply demonstrated, and even an evolutionary approach (formation of a kinetically favored cluster topology followed by slow conversion into a different topology) has been reported , . Here we also investigated cluster self‐assembly in tandem with oxidation of U IV to U VI .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Speciation assignment of these bands was achieved using both isotopic labeling and DFT calculations. These techniques were highlighted in the case of uranyl triperoxide (UO 2 (O 2 ) 3 ) 4− complexes where the ν 1 mode was observed between 738 and 677 cm −1 [140]. Empirical band predictions based upon bond distances do not accurately predict vibrational frequency, indicating a need for additional computational approaches.…”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
“…In summary, while X-ray scattering suggested hydrolysis and condensation reactions occurred in the reaction solutions, full cluster formation was never observed prior to or in tandem with crystallization, which was unexpected based on our experience with other metal-oxo cluster systems. (Falaise and Nyman, 2016; Goberna-Ferrón et al, 2016; Sadeghi et al, 2015) For an additional control experiment, we prepared a solution of the Al13 Keggin ion, per the well-known synthesis. (Johansson, 1960) In this synthesis, 2.6 equivalents of NaOH are added dropwise to a heated aqueous solution of 0.1 molar aluminum nitrate.…”
Section: Computational Studiesmentioning
confidence: 99%